Discourse Markers in News Articles of the Jakarta Post - Yulianto Yulianto (UIR Press, 2021)
Discourse markers facilitate text interpretation. Discourse markers (DMs) were key attributes in linking sentences, rendering the text coherent. This study aimed to analyze Discourse Markers (DMs) found in four News Articles of The Jakarta Post based on Halliday and Hasan point of view. They were additive, adversative, causal and continuative. The writer used a descriptive qualitative method, in which the data were sentences that contain discourse markers in the articles. The data were analyzed by applying the theory of discourse markers from Halliday and Hasan (1976). The result showed there were 21 discourse markers found in four news articles. All the news articles included additive, adversative, causal, and temporal/continuative discourse markers. In the Jakarta Post news article, the numbers of the discourse markers were ample for readers to understand the articles better.